Analisis Yuridis tentang Presidential Threshold di Indonesia - Rezah, Farah Syah; Sapada, Andi Tenri (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to determine the juridical fundamentals and analyze the constitutionality of the provisions of the Presidential Threshold against the 1945 Constitution. The type of research used is normative or doctrinal legal research using a comparative law approach. The method of analysis in this study is to use qualitative analysis. The study results indicate that the Presidential Threshold mechanism in Indonesia has had juridical fundamentals from 2004 until now. In this case, it includes Article 6A section (2) and section (5) of the 1945 Constitution, Article 5 section (4) and Article 101 of Law No. 23 of 2003, Article 9 of Law No. 42 of 2008, to Article 222 of Law No. 7 of 2017. However, Article 222 of Law No. 7 of 2017 is a closed legal policy and not an open legal policy. Therefore, the Presidential Threshold mechanism regulated in Articles of Law up to Article 222 of Law no. 7 of 2017 can be judged unconstitutional or contrary to the 1945 Constitution. Based on this conclusion, it is suggested that the Constitutional Court consider the juridical language of Article 6A section (5) of the 1945 Constitution. In this case, Law No. 7 of 2017 does not contradict the 1945 Constitution. In addition, it is also recommended for Legislators to make amendments to Law No. 7 of 2017. Furthermore, it is hoped that Legislators will consider increasing the Parliamentary Threshold as an effort to strengthen the presidential system in Indonesia.